Statistical atlases and computational models of the heart : Imaging and modelling challenges : 6th International Workshop, STACOM 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 9, 2015, Revised selected papers /: Imaging and modelling challenges : 6th International Workshop, STACOM 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 9, 2015, Revised selected papers. (2016) - Unknown
No abstract available